A NEW NUMERICAL APPROACH FOR SOLVING HIGH-ORDER LINEAR AND NON-LINEAR DIFFERANTIAL EQUATIONS - Secer, Aydin; Altun, Selvi (VINCA INST NUCLEAR SCI, 2018)
In this paper, the Legendre wavelet operational matrix method has been introduced for solving high-order linear and non-linear multi-point: initial and boundary value problems. It has been suggested that the technique is rest upon practical application of the operational matrix and its derivatives. The differential equation is presented that it is converted to a system of algebraic equations via the properties of Legendre wavelet together with the operational matrix method As a result of this study, the scheme has been tested on five linear and non-linear problems. The results have demonstrated that this method is a very effective and advantageous tool in solving such problems.
Keywords: shifted Legendre polynomials; Legendre wavelet; operational matrix; high-order differential equations; BOUNDARY-VALUE-PROBLEMS; DISTRIBUTED-PARAMETER-SYSTEMS; WAVELETS OPERATIONAL MATRIX; DIFFERENTIAL-EQUATIONS; ORTHOGONAL POLYNOMIALS; INTEGRATION; Thermodynamics